The scientific contribution of Malaysia’s researchers in the field of endodontics based on Scopus database : a bibliometric analysis - Lin, Galvin Sim Siang; Leong, JZ; Toh, EY; Leow, YS (Pusat Perubatan Universiti Kebangsaan Malaysia, 2021)
Bibliometric analyses of academic output are critical in assessing a country’s scientific performance and have ignited significant interest in recent days. However, no such study has been conducted in the field of dentistry, specifically endodontics, among Malaysia’s researchers. Hence, this study aimed to assess the publication output among researchers in Malaysia dedicating to endodontics based on the Scopus database and analyse the characteristics of selected articles as well as the publishing patterns. An electronic search based on the Scopus® database was performed from January 2001 to February 2021. Only English language articles with the first author’s affiliation from Malaysia were selected and the following parameters were extracted: title, authors, number of authors, affiliation, journal, year of publication, type of article, source, thematic categories, keywords, and number of citations. Data was analysed using Microsoft Excel software complemented by Pearson’s Chi-square and Pearson Correlation tests at 0.05 significance level. There were 119 articles included with the top-cited article received 69 citations. A total of 15 authors have 2 or more articles published, with the International Endodontic Journal published the most. Furthermore, more than half of the articles were published in Q1 and Q2 journals. Over the last two decades, there has been a substantial growth (P<0.05) in the number of articles and cumulative citations, with a significant correlation (P=0.038) between them. Besides, the Department of Conservative Dentistry and Universiti Sains Malaysia published the most articles, with the bulk of them being basic research on endodontic materials. In conclusion, the rise in scientific publications suggests an increasing interest in endodontics among Malaysia’s researchers.